Improving the Energy Efficiency of a Power Distribution Network by Loss Reduction: A Case Study in Rural 11 Kv Feeder - Khatiwada, Roshan; Bajracharya, Tri Ratna; Khan, Shahbuddin (Journal of Advanced College of Engineering and Management, 2024)
There are inherent losses in transmission and distribution of electrical energy from the generating stations to the ultimate consumer. In this study three different distribution systems viz. IEEE 10 Bus, IEEE 33 Bus Radial Distribution System and a practical Nepalese rural Distribution System are undertaken, and load flow study is carried out to identify the technical loss and various reinforcement techniques are implemented for loss reduction. The technical loss evaluated for 10 Bus, 33 Bus and practical feeder are 5.96%, 5.37% and 12.18% respectively. Capacitor Placement technique was used to study the loss reduction on the standard distribution system which reduced the loss to 5.32% and 3.98% respectively on the 10 Bus and 33 Bus system. Various reinforcement techniques: Conductor Upgradation, Capacitor Placement, Solar PV Integration, Combination of Conductor upgradation & Capacitor Placement; and combination of Solar PV integration and Capacitor Placement were studied on the practical feeder. These methods reduced the 12.18% loss at base case to 11.76%, 8.44%, 8.10%, 7.43%, and 4.22%. This study finds Capacitor Placement to be the most suitable method for loss reduction among the methods studied and similarly combination of conductor upgradation and capacitor placement is also found to be effective solution for loss reduction and efficiency improvement. Other methods undertaken for study are not found to be as effective due to their high investment cost but low returns in terms of loss reductions.